Coating composition

JP2025001085APending Publication Date: 2025-01-08ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023100466
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2025-01-08

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、貯蔵時の着色が少なく、耐薬品性、耐摩耗性、耐傷つき性、ソフトタッチ感に優れ、且つ変色の少ない、塗料組成物を提供するこができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001085000001
    Figure 2025001085000001
  • Figure 2025001085000002
    Figure 2025001085000002
  • Figure 2025001085000003
    Figure 2025001085000003
Patent Text Reader

Abstract

To provide a coating composition which is excellent in chemical resistance, abrasion resistance, scratch resistance and soft touch feeling, and is scarcely changed in color.SOLUTION: A coating composition is provided, containing (a) a curing agent and (b) polycarbonate diol, wherein the component (a) is an organic polyisocyanate compound having 2.6 or more of isocyanate groups in one molecule, the component (b) is a polycondensation product formed by ester exchange reaction of a dihydroxy compound and a carbonate, a number average molecular amount of the component (b) is 250 or more and 3,000 or less, the component (b) contains 1 ppm or more and 25 ppm or less of specific metal (M1), and the component (b) has a Hazen color number of 50 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating composition. [Background technology]

[0002] Conventionally, polyurethane-based paints have been used in a wide range of applications, such as synthetic leather, artificial leather, adhesives, furniture paints, and automotive paints, and polyethers and polyesters are used as polyol components to react with isocyanates (see, for example, Patent Documents 1 and 2). However, in recent years, there has been an increasing demand for paint resistance, such as heat resistance, weather resistance, hydrolysis resistance, mildew resistance, and oil resistance.

[0003] For example, Patent Document 3 proposes polycarbonate diols copolymerized with 1,6-hexanediol and 1,4-butanediol as soft segments with excellent resistance to hydrolysis, light resistance, oxidation deterioration, heat resistance, etc. Coating compositions using these copolymerized polycarbonate diols are said to be capable of providing coating films that are excellent in chemical resistance, abrasion resistance, and scratch resistance, and have a soft touch. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2000-95836 A [Patent Document 2] JP 2001-123112 A [Patent Document 3] Patent Publication No. 2021-75632 Summary of the Invention [Problem to be solved by the invention]

[0005] On the other hand, the polycarbonate diol disclosed in Patent Document 3 uses titanium tetrabutoxide as a polymerization catalyst, so the coating composition made of this polycarbonate diol may be colored during storage due to the influence of the remaining titanium tetrabutoxide residue, and there is room for improvement. In addition, when such a coating composition is used as a clear coating for automobile exteriors, a coating for automobile interiors, a coating for home appliances, a coating for OA products, a surface treatment agent for leather, a surface treatment agent for synthetic leather, etc., as in Patent Document 3, there is a risk of discoloration, and there is room for improvement.

[0006] An object of the present invention is to provide a coating composition which is excellent in chemical resistance, abrasion resistance, scratch resistance and soft touch feeling and which is less susceptible to discoloration. [Means for solving the problem]

[0007] As a result of intensive research, the present inventors have found that by using a specific polycarbonate diol, it is possible to provide a coating composition which is excellent in chemical resistance, abrasion resistance, scratch resistance, and soft touch feeling, and is less susceptible to discoloration, and have thus completed the present invention.

[0008] That is, the present invention includes the following aspects. [1] (a) a curing agent and (b) a polycarbonate diol, The (a) curing agent is an organic polyisocyanate compound having 2.6 or more isocyanate groups in one molecule, The (b) polycarbonate diol is a polycondensate obtained by an ester exchange reaction between a dihydroxy compound and a carbonate ester, The number average molecular weight of the (b) polycarbonate diol is 250 or more and 3000 or less, The (b) polycarbonate diol contains at least one metal (M1) selected from the group consisting of metals in groups 6, 7, 8, 9, 10, and 11 of the long periodic table in a total amount of 1 ppm or more and 25 ppm or less, A coating composition, wherein the polycarbonate diol (b) has a Hazen color number of 50 or less as measured in accordance with JIS-K0071-1 (1998). [2] The coating composition according to [1], wherein the (b) polycarbonate diol contains at least one metal (M2) selected from the group consisting of metals in Group 1 of the long form periodic table in a total amount of 0.1 ppm or more and 12.5 ppm or less. [3] The coating composition according to [1] or [2], wherein the (a) curing agent is a polyisocyanate derived from an aliphatic organic polyisocyanate compound and / or an alicyclic organic polyisocyanate compound. [4] The coating composition according to any one of [1] to [3], which contains an inert organic solvent in an amount of 1 to 90% by mass. [5] The coating composition according to any one of [1] to [4], comprising 1 to 30 mass % of inorganic fine powder having an average particle size of 4 to 15 μm and / or polyurethane particles having an average particle size of 2 to 20 μm, based on the total solid content. [6] A paint-coated molding obtained by coating a molding with the paint composition according to any one of [1] to [5]. Effect of the Invention

[0009] According to the present invention, it is possible to provide a coating composition which exhibits little coloring during storage, excellent chemical resistance, abrasion resistance, scratch resistance, and a soft touch feeling, and which is less susceptible to discoloration. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment for carrying out the present invention (hereinafter, abbreviated as "present embodiment") will be described in detail. Note that the present invention is not limited to the following embodiment, and can be carried out in various modifications within the scope of the gist of the present invention.

[0011] <Paint composition> The coating composition of the present embodiment contains (a) a curing agent and (b) a polycarbonate diol, The (a) curing agent is an organic polyisocyanate compound having 2.6 or more isocyanate groups in one molecule, The (b) polycarbonate diol is a polycondensate obtained by an ester exchange reaction between a dihydroxy compound and a carbonate ester, The number average molecular weight of the (b) polycarbonate diol is 250 or more and 3000 or less, The (b) polycarbonate diol contains at least one metal (M1) selected from the group consisting of metals in groups 6, 7, 8, 9, 10, and 11 of the long periodic table in a total amount of 1 ppm or more and 25 ppm or less, The (b) polycarbonate diol has a Hazen color number of 50 or less as measured in accordance with JIS-K0071-1 (1998).

[0012] The coating composition of the present embodiment is not particularly limited, but can be suitably used, for example, in clear coatings for automobile exteriors, paints for automobile interiors, paints for home appliances, paints for office automation products, surface treatment agents for leather, surface treatment agents for synthetic leather, etc. Clear coatings for automobile exteriors, paints for automobile interiors, paints for home appliances, paints for office automation products, surface treatment agents for leather, surface treatment agents for synthetic leather, etc., prepared using the coating composition of the present embodiment are characterized by little discoloration.

[0013] <(a) Hardener> The (a) curing agent used in this embodiment is an organic polyisocyanate compound having 2.6 or more isocyanate groups in one molecule. As the curing agent (a), particularly from the viewpoint of weather resistance, polyisocyanates derived from an aliphatic organic diisocyanate compound and / or an alicyclic organic diisocyanate compound are preferred, and specific examples include, but are not limited to, polyisocyanates derived from aliphatic or alicyclic diisocyanates such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), etc. Furthermore, so-called blocked isocyanate-based curing agents in which these polyisocyanates are blocked with known blocking agents such as butanol, 2-ethylhexanol, and other lower alcohols, methyl ethyl ketone oxime, lactams, phenols, imidazoles, and active methylene compounds can also be used. These polyisocyanate compounds are not particularly limited, but examples thereof include Sumidur 44S, 44V70 (both manufactured by Sumika Bayer Urethane), Dismodur HL (manufactured by Sumika Bayer Urethane), which is a copolymer of TDI and HDI, and various Duranates manufactured by Asahi Kasei Corporation, namely, Duranate 24A-100, Duranate 22A-75PX, Duranate 18H-70B, Duranate 21S-75E, Duranate THA-100, Duranate TPA-100, Duranate MFA-75X, Duranate TSA-100, Duranate TSS-100, Duranate ... Duranate TSE-100, Duranate D-101, Duranate D-201, Duranate P-301-75E, Duranate E-402-90T, Duranate E-402-90T, Duranate E-405-80T, Duranate ME20-100, Duranate 17B-60PX, Duranate TPA-B80X, Duranate MF-B60X, Duranate E-402-B80T, Duranate ME20-B80S, Duranate WB40-100, Duranate WB40-80D, Duranate WT20-100, Duranate WT30-100, and the like.From the viewpoint of improving the acid resistance, alkali resistance, alcohol resistance, oil resistance, abrasion resistance, and scratch resistance of the cured coating film, the organic polyisocyanate compound is preferably a polyisocyanate derived from an aliphatic organic isocyanate compound and / or an alicyclic organic isocyanate compound having 2.6 or more isocyanate groups and / or blocked isocyanate groups in one molecule, and specifically, diisocyanate derivatives such as biuret, allophanate, uretdione, and isocyanurate, and polyhydric alcohol adduct types are more preferred.

[0014] In the organic polyisocyanate compound, the lower limit of the number of isocyanate groups in one molecule is 2.6, more preferably 2.8, and even more preferably 3.0, and the upper limit is preferably 8.0, more preferably 6.0, and even more preferably 4.0.

[0015] In the present embodiment, the number of isocyanate groups (average number of functional groups) in one molecule of the organic polyisocyanate compound can be calculated from the isocyanate group content (mass%) determined by the method described in JIS K7301-1995 and the number average molecular weight of the organic polyisocyanate determined by measuring the number average molecular weight based on polystyrene standard by gel permeation chromatography (GPC) using the following formula (I).

[0016] Average number of functional groups = number average molecular weight of organic polyisocyanate × isocyanate group content (mass%) / 100% / 42 (I)

[0017] The specific analytical methods for the isocyanate group content and the number average molecular weight of the organic polyisocyanate are as follows.

[0018] (Physical property 1) Isocyanate group content The polyisocyanate composition is used as a sample, and the isocyanate group content is measured according to the method described in JIS K7301-1995 (Test method for tolylene diisocyanate prepolymer for thermosetting urethane elastomer). A more specific method for measuring the isocyanate group content is described below. (1) Place 1 g of sample in a 200 mL Erlenmeyer flask, add 20 mL of toluene to the flask, and dissolve the sample. (2) Then, add 20 mL of 2.0 N di-n-butylamine-toluene solution to the flask and let stand for 15 minutes. (3) 70 mL of 2-propanol is added to the flask and dissolved to obtain a solution. (4) The solution obtained in (3) above is titrated with 1 mol / L hydrochloric acid to determine the sample titer. (5) Even if no sample is added, measurements are carried out in the same manner as in (1) to (3) above to determine the blank titer.

[0019] The isocyanate group content is calculated from the sample titer and blank titer determined above according to the following formula (II).

[0020] Isocyanate group content (mass%) = (blank titration amount - sample titration amount) x 42 / [sample mass (g) x 1,000] x 100%. (II)

[0021] (Property 2) Number average molecular weight of organic polyisocyanate Using a polyisocyanate composition as a sample, the number average molecular weight of the polyisocyanate including the modified polyisocyanate and the unreacted polyisocyanate in the polyisocyanate composition is measured by gel permeation chromatography (GPC) using the following apparatus and conditions, based on the number average molecular weight of polystyrene standard. Equipment: Tosoh Corporation HLC-8120GPC (product name) Column: TSKgelSuperH1000 (product name) x 1, TSKgelSuperH2000 (product name) x 1, TSKgelSuperH3000 (product name) x 1, manufactured by Tosoh Corporation Carrier: Tetrahydrofuran Detection method: Differential refractometer

[0022] (Property 3) Average number of isocyanate functional groups Using a polyisocyanate composition as a sample, the average number of isocyanate functional groups is the number of isocyanate functional groups statistically contained in one molecule of polyisocyanate, and is calculated from the number average molecular weight of the organic polyisocyanate measured in (Physical Property 2) and the isocyanate group content measured in (Physical Property 1) according to the following formula (III).

[0023] Average functionality = number average molecular weight of organic polyisocyanate × isocyanate group content (mass%) / 100% / 42 (III)

[0024] <2.(b) Polycarbonate diol> The method for producing the polycarbonate diol (b) used in the coating composition of the present embodiment is not particularly limited, but includes, for example, a step of obtaining a polycarbonate diol by polycondensation by transesterification in the presence of a transesterification catalyst using a dihydroxy compound and a carbonate ester as raw material monomers, and the transesterification catalyst preferably contains at least one metal (M1) selected from the group consisting of metals of Groups 6, 7, 8, 9, 10 and 11 of the long-period periodic table. The method for producing the polycarbonate diol (b) used in the coating composition of the present embodiment uses a transesterification catalyst containing a specific metal in this way, and can efficiently produce the polycarbonate diol (b) used in the coating composition of the present embodiment. When used in the coating composition of the present embodiment, the coating composition is less colored, and when used in, for example, clear coating for automobile exteriors, coating for automobile interiors, coating for home appliances, coating for OA products, surface treatment agent for leather, surface treatment agent for synthetic leather, etc., it is preferable because it can provide a coating composition that is less discolored.

[0025] In addition, it is more efficient (specifically, for example, under milder reaction conditions and in a shorter time) and more preferable that the transesterification catalyst comprises a transesterification catalyst A1 containing at least one metal (M1) selected from the group consisting of metals in Groups 6, 7, 8, 9, 10 and 11 of the long-form periodic table, and a transesterification catalyst A2 containing at least one metal (M2) selected from the group consisting of metals in Group 1 of the long-form periodic table.

[0026] The method for producing the polycarbonate diol (b) used in the coating composition of this embodiment uses at least two types of transesterification catalysts containing specific metals, which allows efficient production of the polycarbonate diol (b) used in the coating composition of this embodiment. When used in the coating composition of this embodiment, the polycarbonate diol is less discolored, and is more preferable because it provides a coating composition that is less discolored when used, for example, in clear paint for automobile exteriors, paint for automobile interiors, paint for home appliances, paint for office automation products, surface treatment agents for leather, surface treatment agents for synthetic leather, etc.

[0027] <2-1. Raw material monomer> In the method for producing the polycarbonate diol (b) of this embodiment, a dihydroxy compound and a carbonate ester are used as raw material monomers.

[0028] <2-1-1. Dihydroxy compounds> In the method for producing a polycarbonate diol according to the present embodiment, the dihydroxy compound serving as a raw material monomer is not particularly limited, and examples thereof include linear terminal dihydroxy compounds such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, and 1,20-eicosanediol; dihydroxy compounds having an ether group such as diethylene glycol, triethylene glycol, tetraethylene glycol, polypropylene glycol, and polytetramethylene glycol; thioether diols such as bishydroxyethyl thioether; 2-ethyl-1,6-hexanediol, 2-methyl-1,3-propanediol, 2,2-Dialkyl-substituted 1,3-propanediol such as 3-methyl-1,5-pentanediol, 2-methyl-1,8-octanediol, 2,4-diethyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol (hereinafter sometimes abbreviated as neopentyl glycol), 2-ethyl-2-butyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, and 2-pentyl-2-propyl-1,3-propanediol propanediols (hereinafter sometimes referred to as 2,2-dialkyl-1,3-propanediols); tetraalkyl-substituted alkylenediols such as 2,2,4,4-tetramethyl-1,5-pentanediol and 2,2,9,9-tetramethyl-1,10-decanediol, and dihydroxy compounds containing a cyclic group such as 3,9-bis(1,1-dimethyl-2-hydroxyethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane;Dihydroxy compounds having branched chains such as 2,2-diphenyl-1,3-propanediol, 2,2-divinyl-1,3-propanediol, 2,2-diethynyl-1,3-propanediol, 2,2-dimethoxy-1,3-propanediol, bis(2-hydroxy-1,1-dimethylethyl)ether, bis(2-hydroxy-1,1-dimethylethyl)thioether, and 2,2,4,4-tetramethyl-3-cyano-1,5-pentanediol; 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 4,4-dicyclohexyldimethylmethanediol, 2,2'-bis(4-hydroxycyclohexyl)propane, 1,4-di Dihydroxy compounds having a cyclic group in the molecule, such as hydroxyethylcyclohexane, isosorbide, spiroglycol, 2,5-bis(hydroxymethyl)tetrahydrofuran, 4,4'-isopropylidenedicyclohexanol, and 4,4'-isopropylidenebis(2,2'-hydroxyethoxycyclohexane); dihydroxy compounds having an aromatic ring, such as 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy-2-methyl)phenyl)fluorene, nitrogen-containing dihydroxy compounds, such as diethanolamine and N-methyl-diethanolamine; and sulfur-containing dihydroxy compounds, such as bis(hydroxyethyl)sulfide;2,2-bis(4-hydroxyphenyl)propane [=bisphenol A], 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-diethylphenyl)propane, 2,2-bis(4-hydroxy-(3,5-diphenyl)phenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis(4-hydroxyphenyl)pentane, 2,4'-dihydroxy-diphenylmethane, bis(4-hydroxyphenyl)methane, bis(4-hydroxy-5-nitrophenyl)methane, 1,1-bis(4-hydroxyphenyl)pentane, bis(4-hydroxyphenyl)methane, bis(4-hydroxy-5-nitrophenyl)methane, bis(4-hydroxyphenyl)pentane ... aromatic bisphenols such as bis(4-hydroxyphenyl)ethane, 3,3-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)sulfone, 2,4'-dihydroxydiphenylsulfone, bis(4-hydroxyphenyl)sulfide, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dichlorodiphenyl ether, 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-2-methylphenyl)fluorene;

[0029] In particular, from the viewpoint of the weather resistance of the coating composition containing the polycarbonate diol used in this embodiment, the dihydroxy compound is preferably at least one compound selected from the group consisting of aliphatic dihydroxy compounds and alicyclic dihydroxy compounds represented by the following formula (1). [ka] (In the formula, R1 represents a divalent aliphatic or alicyclic hydrocarbon having 2 to 20 carbon atoms.)

[0030] Among these dihydroxy compounds, the aliphatic dihydroxy compounds are particularly preferably 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 1,10-decanediol, neopentyl glycol, 2-methyl-1,3-propanediol, 3-methyl-1,5-pentanediol, and 2-methyl-1,8-octanediol, and the alicyclic dihydroxy compounds are particularly preferably 1,4-cyclohexanedimethanol and tricyclodecanedimethanol.Of these dihydroxy compounds, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol are more preferred because they provide excellent softness to the coating film using the resulting coating composition.

[0031] These dihydroxy compounds may be used alone or in combination of two or more depending on the required performance of the resulting polycarbonate diol, but it is preferable to combine a plurality of them to form a copolymer polycarbonate diol. The copolymer polycarbonate diol is generally inhibited from crystallizing, and has higher fluidity than homopolycarbonate diol, and is excellent in operability when processed into a coating composition, and can impart flexibility and texture (softness) to a coating film using the coating composition.

[0032] Regarding the composition ratio of copolymerization, for example, when two kinds of dihydroxy compounds are used, each dihydroxy compound is preferably used at 5 mol% or more, preferably 10 mol% or more, more preferably 20 mol% or more, and even more preferably 30 mol% or more, based on the total dihydroxy compounds. When two or more kinds of dihydroxy compounds are used, it is more preferable to use at least two kinds of dihydroxy compounds selected from 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol, because the coating film using the obtained coating composition has excellent flexibility and texture (soft feeling).

[0033] <2-1-2. Carbonate ester> In the method for producing the polycarbonate diol (b) used in the coating composition of this embodiment, the carbonate ester usable as the raw material monomer is not limited as long as the effect of the present invention is not lost, and examples thereof include dialkyl carbonate, diaryl carbonate, and alkylene carbonate.

[0034] Among the carbonate esters that can be used in the method for producing the polycarbonate diol (b) used in this embodiment, specific examples of dialkyl carbonates are not particularly limited, but include, for example, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, dicyclohexyl carbonate, diisobutyl carbonate, ethyl-n-butyl carbonate, and ethyl isobutyl carbonate.

[0035] Examples of diaryl carbonates include, but are not limited to, diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, di-m-cresyl carbonate, and the like.

[0036] Examples of alkylene carbonates include, but are not limited to, ethylene carbonate, trimethylene carbonate, tetramethylene carbonate, 1,2-propylene carbonate, 1,2-butylene carbonate, 1,3-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 1,3-pentylene carbonate, 1,4-pentylene carbonate, 1,5-pentylene carbonate, 2,3-pentylene carbonate, 2,4-pentylene carbonate, and neopentyl carbonate. These may be used alone or in combination of two or more.

[0037] Among these carbonate esters, dimethyl carbonate, diethyl carbonate, ethylene carbonate, and diphenyl carbonate are preferred because they are inexpensively available as industrial raw materials, have good reactivity, and produce small amounts of alcohol as by-products. Ethylene carbonate is particularly preferred because it gives a coating film with excellent toughness.

[0038] <2-1-3. Usage ratio of raw material monomers> In the method for producing the polycarbonate diol (b) used in this embodiment, the amount of carbonate ester used must be appropriately changed depending on the target molecular weight of the polycarbonate diol, and is not particularly limited, but the molar ratio relative to 1 mole of the total of dihydroxy compounds is usually 0.5, preferably 0.7, more preferably 0.8, and 1.5, preferably 1.3, more preferably 1.2 in lower limit, preferably 0.7, more preferably 0.8, and upper limit is preferably 1.5, preferably 1.3, more preferably 1.2. When the amount of carbonate diester used is less than the upper limit, the proportion of the terminal group of the obtained polycarbonate diol that is not a hydroxyl group can be suppressed, or the polycarbonate diol of this embodiment having a molecular weight in a predetermined range tends to be produced, and when the amount is more than the lower limit, the polymerization tends to proceed to a predetermined molecular weight.

[0039] <2-2. Transesterification catalyst> The method for producing the polycarbonate diol (b) used in the present embodiment is not particularly limited, but it is preferable to use an ester exchange catalyst containing at least one metal (M1) selected from the group consisting of metals of Groups 6, 7, 8, 9, 10 and 11 of the long form periodic table.

[0040] One form of the transesterification catalyst containing at least one metal (M1) selected from the group consisting of metals of Groups 6, 7, 8, 9, 10 and 11 of the long form periodic table is preferably at least one metal complex and / or a hydrate thereof represented by the following formula (2): [ka] (In the formula, R2 and R4 each independently represent a monovalent hydrocarbon group having 1 to 10 carbon atoms, and the hydrocarbon group of R2 and R4 may be substituted with a halogen atom or may have an oxygen atom; R3 represents hydrogen or a monovalent hydrocarbon group having 1 to 10 carbon atoms, and the hydrocarbon group of R3 may be substituted with a halogen atom or may have an oxygen atom; M1 represents at least one metal selected from the group consisting of metals of groups 6, 7, 8, 9, 10 and 11 of the long form periodic table; and n is 1, 2 or 3. The metal complex represented by formula (2) may be an association of a plurality of metals.)

[0041] The metal (M1) selected from the group consisting of groups 6, 7, 8, 9, 10 and 11 of the long form periodic table is not particularly limited, but from the viewpoint of catalytic activity, molybdenum, manganese, iron, cobalt, nickel and copper are preferred, and among these, manganese is particularly preferred.

[0042] In addition, together with the transesterification catalyst represented by formula (2), it is also possible to use, as an auxiliary, a basic compound such as a transition metal compound, a basic boron compound, a basic phosphorus compound, a basic ammonium compound, or an amine compound.

[0043] In the present embodiment, the organometallic complexes with acetylacetone analogues used as transesterification catalysts can also be used as hydrates.

[0044] Another embodiment of the transesterification catalyst containing at least one metal (M1) selected from the group consisting of metals in groups 6, 7, 8, 9, 10, and 11 of the long periodic table is preferably a salt of at least one carboxylic acid and at least one metal (M1) selected from the group consisting of metals in groups 6, 7, 8, 9, 10, and 11 of the long periodic table and / or a hydrate thereof, as represented by the following formula (3):

[0045] [ka] (In the formula, R5 represents a monovalent hydrocarbon group having 1 to 20 carbon atoms, and the hydrocarbon group of R5 may be substituted with a halogen atom or may have an oxygen atom.)

[0046] The carboxylic acid is not particularly limited, but examples thereof include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, palmitic acid, margaric acid, stearic acid, and the like. Of these, acetic acid, propionic acid, and butyric acid are preferred, and acetic acid is particularly preferred.

[0047] The metal (M1) selected from the group consisting of groups 6, 7, 8, 9, 10 and 11 of the long form periodic table is not particularly limited, but from the viewpoint of catalytic activity, molybdenum, manganese, iron, cobalt, nickel and copper are preferred, and among these, manganese is particularly preferred.

[0048] In the present embodiment, the salts of these carboxylic acids used as the transesterification catalyst may also be used as hydrates.

[0049] The amount of the transesterification catalyst used in this embodiment is, as the total amount of the metal (M1), preferably 0.5 ppm to 20 ppm, more preferably 0.5 ppm to 15 ppm, even more preferably 0.5 ppm to 10 ppm, and also preferably 1 ppm to 20 ppm, more preferably 3 ppm to 20 ppm, and even more preferably 5 ppm to 20 ppm. When the amount of the transesterification catalyst used is 0.5 ppm or more in total as the metal (M1), the reaction rate of the transesterification tends to be faster. In addition, when the amount of the transesterification catalyst used is 20 ppm or less in total as the metal (M1), coloration of the obtained polycarbonate diol can be suppressed, and when used as a raw material for the coating composition of the present embodiment, the curing reaction tends to be stable. For example, when used in clear coatings for automobile exteriors, coatings for automobile interiors, coatings for home appliances, coatings for office automation products, surface treatment agents for leather, surface treatment agents for synthetic leather, etc., the coating composition of the present embodiment with less discoloration can be provided, which is more preferable.

[0050] The method for producing the polycarbonate diol (b) used in the coating composition of the present embodiment is not particularly limited, but it is more preferable to use the above-mentioned transesterification catalyst A1 in combination with a transesterification catalyst A2 containing at least one metal (M2) selected from the group consisting of metals in Group 1 of the long form periodic table.

[0051] The metal of Group 1 of the long periodic table is not particularly limited, but examples thereof include lithium, sodium, potassium, rubidium, cesium, and francium. Among these, lithium, sodium, and potassium are preferred because of their high catalytic activity. Lithium is particularly preferred because it has high activity and produces a polycarbonate diol with a small amount of ether bonds.

[0052] The form of the transesterification catalyst A2 containing at least one metal (M2) selected from the group consisting of metals in Group 1 of the long form periodic table is not particularly limited, and examples thereof include salts with inorganic acids, salts with organic acids, alcoholates of various alcohols, and hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide, and titanium hydroxide.

[0053] Among these, an alcoholate of at least one alcohol and at least one metal (M2) selected from the group consisting of metals in Group 1 of the long form periodic table, as represented by the following formula (4), is preferred because it has high catalytic activity and little coloration. [ka] (In the formula, R6 represents a monovalent hydrocarbon group having 1 to 20 carbon atoms, and the hydrocarbon group of R6 may be substituted with a halogen atom or may have an oxygen atom.)

[0054] The alcoholate of at least one alcohol and a metal of Group 1 of the long periodic table represented by formula (4) is not particularly limited, and examples thereof include lithium methylate (lithium methoxide), lithium ethylate (lithium ethoxide), lithium propoxide, lithium butoxide, sodium methylate (sodium methoxide), sodium ethylate (sodium ethoxide), sodium propoxide, sodium butoxide, potassium methylate (potassium methoxide), potassium ethylate (potassium ethoxide), potassium propoxide, potassium butoxide, rubidium methoxide, rubidium ethoxide, cesium methoxide, cesium ethoxide, etc. Among these alcoholates, lithium methylate, lithium ethylate, sodium methylate, and sodium ethylate are preferred, as they have high catalytic activity and produce polycarbonate diol with a small amount of ether bonds and little coloring, and lithium methylate and lithium ethylate are particularly preferred.

[0055] In the method for producing the polycarbonate diol (b) used in the coating composition of the present embodiment, there is no particular limitation, but when at least two kinds of transesterification catalysts, namely, a transesterification catalyst A1 containing at least one metal (M1) selected from the group consisting of metals of Groups 6, 7, 8, 9, 10 and 11 of the long periodic table, and a transesterification catalyst A2 containing at least one metal (M2) selected from the group consisting of metals of Group 1 of the long periodic table, are used in combination, the amount of the transesterification catalyst A1 used is, as the total amount of the metal (M1), preferably 0.5 ppm or more and 20 ppm or less, more preferably 1 ppm or more and 20 ppm or less, and even more preferably 2 ppm or more and 20 ppm or less, based on the total amount of all dihydroxy compounds and carbonate esters. The total amount of the transesterification catalyst A2 used, as the metal (M2), is preferably 0.05 ppm to 10 ppm, more preferably 0.1 ppm to 10 ppm, and even more preferably 1 ppm to 10 ppm, based on the total amount of all dihydroxy compounds and carbonates. The total amount of the transesterification catalyst A2 used, as the metal (M2), is preferably 0.05 ppm to 10 ppm, more preferably 0.05 ppm to 5 ppm, and even more preferably 0.05 ppm to 3 ppm, based on the total amount of all dihydroxy compounds and carbonates.

[0056] When the amount of transesterification catalyst A1 used is 0.5ppm or more in total amount as metal (M1), the reaction rate of transesterification tends to be faster.In addition, when the amount of transesterification catalyst is 20ppm or less in total amount as metal (M1), the coloring of (b) polycarbonate diol used in the coating composition is small during storage, and when it is used in, for example, clear coating for automobile exterior, coating for automobile interior, coating for home appliances, coating for OA products, surface treatment agent for leather, surface treatment agent for synthetic leather, etc., it is more preferable because it can provide a coating composition with little discoloration.

[0057] In addition, when the amount of the transesterification catalyst A2 used is 0.05 ppm or more in total as metal (M2), the reaction rate of transesterification tends to be faster. In addition, when the amount of the transesterification catalyst is 10 ppm or less in total as metal (M2), the coloring of the obtained polycarbonate diol can be suppressed, and it is more preferable that the coating composition with little discoloration can be provided when used, for example, in clear coating for automobile exterior, coating for automobile interior, coating for home appliances, coating for OA products, surface treatment agent for leather, surface treatment agent for synthetic leather, etc.

[0058] <2-3.(b) Method for producing polycarbonate diol> In this embodiment, it is preferable to produce a polycarbonate diol by transesterifying one or more of the dihydroxy compounds described above with one or more of the carbonate esters described above in the presence of the transesterification catalyst described above.

[0059] <2-3-1. Reaction conditions, etc.> The method for charging the reaction raw materials is not particularly limited, and the method can be freely selected from the following methods: one or more dihydroxy compounds, a carbonate ester, and a catalyst are all charged at the same time and subjected to a reaction; when the carbonate ester is a solid, the carbonate ester is first charged and heated to melt, and then the dihydroxy compound and the catalyst are added; and conversely, when the dihydroxy compound is a solid, the dihydroxy compound is first charged and melted, and then the carbonate ester and the catalyst are added.

[0060] The reaction temperature during the transesterification reaction can be arbitrarily selected as long as it is a temperature at which a practical reaction rate can be obtained. The temperature is not particularly limited, but the lower limit is preferably 80°C, more preferably 110°C, and even more preferably 130°C. The upper limit of the reaction temperature is preferably 220°C, more preferably 200°C, even more preferably 180°C, and particularly preferably 170°C. When the reaction temperature is equal to or higher than the lower limit, the transesterification reaction tends to proceed at a practical rate. When the reaction temperature is equal to or lower than the upper limit, the coloring of the resulting polycarbonate diol can be suppressed, the formation of ether bonds can be suppressed, and the quality tends to improve, such as the turbidity being good.

[0061] In particular, the method for producing the polycarbonate diol (b) used in the coating composition of the present embodiment uses a transesterification catalyst containing a specific metal (M1) and having higher activity than conventional methods, and thereby can efficiently produce polycarbonate diol in a short time under mild reaction conditions, for example, at a low temperature of 160°C or lower (preferably 150°C or lower).

[0062] The reaction can be carried out at normal pressure, but the transesterification reaction is an equilibrium reaction, and the reaction can be biased toward the product system by distilling off the monohydroxy compound or dihydroxy compound produced outside the system. Therefore, it is usually preferable to adopt reduced pressure conditions in the latter half of the reaction to carry out the reaction while distilling off the monohydroxy compound or dihydroxy compound produced. Alternatively, it is also possible to carry out the reaction while distilling off the monohydroxy compound or dihydroxy compound produced by gradually lowering the pressure from the middle of the reaction. If the pressure is gradually lowered from the middle of the reaction, the volatilization of the low-boiling unreacted monomer can be suppressed, the yield is improved, and a polycarbonate diol with a predetermined molecular weight is obtained, or in the case of copolymerization, a polycarbonate diol with a predetermined copolymerization composition ratio is obtained.

[0063] The pressure during the reaction is appropriately selected depending on the type of alcohol derived from the carbonate ester to be distilled, and for example, when the alcohol to be distilled has a relatively low boiling point such as methanol, the pressure of the reactor is preferably 5 kPa to normal pressure, more preferably 7 kPa to 15 kPa. When the alcohol to be distilled has a relatively high boiling point such as ethylene glycol, the pressure of the reactor is preferably 1 to 10 kPa, more preferably 3 kPa to 7 kPa.

[0064] Furthermore, in order to prevent the distillation of the raw materials in the early stage of the reaction, the reactor may be equipped with a rectification column having a theoretical number of 10 or more, preferably 15 or more, and more preferably 20 or more, so that the monohydroxy compound or dihydroxy compound produced by the reaction from the carbonate ester can be efficiently separated and distilled off while refluxing and separating the raw material carbonate ester and dihydroxy compound, by azeotropy. In this case, the raw material monomers charged are not lost and the quantitative ratio of the reagents can be accurately adjusted, which is preferable.

[0065] In addition, at the final stage of the reaction, it is usually preferable to switch to simple distillation and increase the degree of vacuum to carry out the reaction, since this makes it possible to efficiently distill off by-produced alcohols, diols, phenols, and other monohydroxy compounds or dihydroxy compounds, residual monomers such as carbonate esters, and further cyclic carbonates (cyclic oligomers) which may cause turbidity.

[0066] In this case, the reaction pressure at the end of the reaction is not particularly limited, but the upper limit is usually preferably 5 kPa, more preferably 2 kPa, further preferably 1 kPa or less, and further preferably 0.5 kPa or less. In order to effectively distill off these low-boiling components, the reaction can also be carried out while passing a small amount of an inert gas such as nitrogen, argon, or helium into the reaction system.

[0067] When a carbonate ester or a dihydroxy compound having a low boiling point is used in the transesterification reaction, the reaction may be carried out at a temperature close to the boiling point of the carbonate diester or dihydroxy compound in the early stage of the reaction, and the temperature may be gradually increased as the reaction proceeds to further proceed. This is preferable because it is possible to prevent the distillation of the unreacted carbonate diester or dihydroxy compound in the early stage of the reaction.

[0068] <2-3-2. Polymerization reactor> The polymerization reaction (polycondensation reaction) can be carried out either batchwise or continuously. The apparatus used may be any of tank, tube, and tower types, and known polymerization tanks equipped with various stirring blades can be used. There are no particular limitations on the atmosphere during the temperature rise of the apparatus, but from the viewpoint of product quality, it is preferable to carry out the reaction in an inert gas such as nitrogen gas under normal pressure or reduced pressure.

[0069] <2-3-3. Reaction time> In the method for producing the polycarbonate diol (b) used in the coating composition of this embodiment, the time required for the ester exchange reaction (polymerization reaction or polycondensation reaction) varies greatly depending on the types and amounts of the dihydroxy compound, carbonic acid diester, and ester exchange catalyst used, so it cannot be generally specified, but the reaction time required to reach a predetermined molecular weight is preferably 30 hours or less, more preferably 20 hours or less, and even more preferably 10 hours or less.

[0070] <2-3-4. Catalyst deactivation> As described above, when a transesterification catalyst is used in the transesterification reaction, the transesterification catalyst or its residue remains in the polycarbonate diol obtained, which may cause discoloration because the reaction cannot be controlled during the polyurethane reaction. In order to suppress the influence of the remaining catalyst, a catalyst deactivator, such as an acidic compound or a phosphorus-based or sulfur-based compound that decomposes to an acidic compound, may be added in an amount approximately equal to the molar amount of the transesterification catalyst used. Furthermore, if the catalyst is heated after the addition as described below, the transesterification catalyst can be efficiently deactivated. In addition, the color development derived from the transesterification catalyst can be reduced by deactivating the catalyst, and a polycarbonate diol can be obtained in which the Hazen color number measured in accordance with JIS-K0071-1 (1998) is preferably 50 or less, more preferably 30 or less, and even more preferably 20 or less.

[0071] In addition, the addition of a catalyst deactivator can suppress coloration and changes in physical properties that occur due to changes in the terminal structure and skeleton of the polycarbonate diol and the remaining catalyst when the obtained polycarbonate diol composition is stored or handled at high temperature for a long period of time.

[0072] The compound used for inactivating the transesterification catalyst (hereinafter sometimes referred to as a catalyst deactivator) is not particularly limited, but examples thereof include inorganic phosphoric acids such as phosphoric acid and phosphorous acid, organic phosphoric acid esters such as monobutyl phosphate, dibutyl phosphate, tributyl phosphate, trioctyl phosphate, triphenyl phosphate, and triphenyl phosphite, sulfonic acid, sulfonate esters, etc. These may be used alone or in combination of two or more.

[0073] The amount of the catalyst deactivator used is not particularly limited, but as described above, it is sufficient that the amount is approximately equimolar to the amount of the transesterification catalyst used. Specifically, the lower limit is preferably 0.8 mol, more preferably 1.0 mol, and the upper limit is preferably 5 mol, more preferably 2 mol, relative to 1 mol of the transesterification catalyst used.

[0074] Inactivation of the transesterification catalyst by adding a catalyst deactivator can be carried out at room temperature, but it is more efficient when heated. The temperature of this heat treatment is not particularly limited, but the lower limit is preferably 80°C, more preferably 100°C, and even more preferably 110°C, and the upper limit is preferably 140°C, more preferably 130°C, and even more preferably 120°C. At temperatures above the lower limit, the time required for deactivation of the transesterification catalyst is short and efficient, and the degree of deactivation is also sufficient. On the other hand, at temperatures below the upper limit, when a phosphorus-based compound is used as a deactivator, the decomposition of the phosphorus-based compound can be suppressed, and deactivation tends to be stable. Therefore, coloration of the resulting polycarbonate diol can be suppressed, and when used as a coating composition, the curing reaction tends to be stable.

[0075] The time for the reaction with the catalyst deactivator is not particularly limited, but is, for example, 1 to 5 hours.

[0076] <2-4.(b) Physical properties of polycarbonate diol> Preferred physical properties of the polycarbonate diol (b) used in the coating composition of this embodiment are described below.

[0077] <2-4-1.Molecular weight / molecular weight distribution> The lower limit of the number average molecular weight (Mn) of the polycarbonate diol (b) used in the coating composition of this embodiment is 250, preferably 500, more preferably 750, and even more preferably 1000. On the other hand, the upper limit of the number average molecular weight (Mn) of the polycarbonate diol (b) used in the coating composition of this embodiment is 3000, preferably 2500, more preferably 2100, and particularly preferably 2000. If the number average molecular weight of the polycarbonate diol is not less than the above lower limit, the coating film using the coating composition of this embodiment has excellent flexibility and texture (softness), which is more preferable. On the other hand, if the number average molecular weight of the polycarbonate diol is not more than the above upper limit, the viscosity of the polycarbonate diol decreases, and handling during the production of the coating composition tends to be easier.

[0078] The number average molecular weight (Mn) of the polycarbonate diol (b) used in this embodiment is preferably in the range of 250 to 3,000, more preferably 500 to 2,500, further preferably 750 to 2,100, and particularly preferably 1,000 to 2,000.

[0079] Here, the number average molecular weight of the polycarbonate diol is determined from the hydroxyl value (average hydroxyl value) of the polycarbonate diol, as shown in the examples given later.

[0080] The method for controlling the number average molecular weight (Mn) of the polycarbonate diol within the above range is not particularly limited, but examples thereof include a method for controlling the number average molecular weight (Mn) of the polycarbonate diol within the above range by adjusting the polycondensation reaction time of the polycarbonate diol and adjusting the amount of the dihydroxy compound, which is a raw material monomer, to be extracted.

[0081] <2-4-2.APHA value> The color of the polycarbonate diol (b) used in the coating composition of this embodiment is preferably 50 or less in terms of the Hazen color number (based on JIS K0071-1:1998), more preferably 40 or less, even more preferably 30 or less, and particularly preferably 20 or less. The lower limit of the APHA value of the polycarbonate diol (b) is not particularly limited, but is, for example, 0 or more. When the APHA value of the polycarbonate diol (b) is 50 or less, the color tone of the coating composition obtained using the polycarbonate diol as a raw material tends to be good, the commercial value is improved, and the thermal stability tends to be good. The preferred range of the APHA value of the polycarbonate diol (b) is 10 to 50, preferably 10 to 40, and more preferably 10 to 30.

[0082] The method for controlling the APHA value of the polycarbonate diol within the above range is not particularly limited, but examples thereof include a method in which the reaction temperature during the ester exchange reaction is within the above preferred temperature range, and a method in which the time required for the ester exchange reaction (polymerization reaction or polycondensation reaction) is within the above preferred range.

[0083] In this embodiment, the APHA value of the polycarbonate diol can be measured by the method described in the Examples below.

[0084] <2-4-3. Metals contained in polycarbonate diol> The (b) polycarbonate diol used in the coating composition of this embodiment preferably contains at least one metal (M1) selected from the group consisting of metals in groups 6, 7, 8, 9, 10 and 11 of the long form periodic table.

[0085] In the (b) polycarbonate diol used in the coating composition of this embodiment, the lower limit of the total amount of at least one metal (M1) selected from the group consisting of metals in groups 6, 7, 8, 9, 10 and 11 of the long periodic table is 1 ppm, preferably 2 ppm, more preferably 5 ppm, and the upper limit is 25 ppm, preferably 20 ppm, more preferably 15 ppm, and even more preferably 10 ppm. In the polycarbonate diol of the present embodiment, at least one metal (M1) selected from the group consisting of metals of Groups 6, 7, 8, 9, 10, and 11 of the long periodic table is preferably contained in a total amount of 1 ppm to 25 ppm, more preferably 2 ppm to 25 ppm, and even more preferably 5 ppm to 25 ppm, and preferably 1 ppm to 25 ppm, more preferably 2 ppm to 25 ppm, and even more preferably 5 ppm to 25 ppm.

[0086] The (b) polycarbonate diol used in the coating composition of this embodiment has a metal (M1) content of 1 ppm or more in total, and when used as a raw material for the coating composition of this embodiment, the APHA value is low, and the reaction rate of curing tends to improve. In addition, the (b) polycarbonate diol used in the coating composition of this embodiment has a metal (M1) content of 25 ppm or less in total, which can suppress the coloring of the (b) polycarbonate diol caused by heating, and is less colored during storage. In addition, it is more preferable to provide a coating composition that is less discolored when used, for example, as a clear coating for automobile exteriors, a coating for automobile interiors, a coating for home appliances, a coating for OA products, a surface treatment agent for leather, a surface treatment agent for synthetic leather, etc.

[0087] The polycarbonate diol (b) used in the coating composition of the present embodiment preferably contains at least one metal (M1) selected from molybdenum, manganese, iron, cobalt, nickel, and copper. Among these, the metal is more preferably manganese.

[0088] The metals contained in the polycarbonate diol (b) may be present as a residue of the polymerization catalyst, but may also be intentionally added in a predetermined amount after production.

[0089] In the (b) polycarbonate diol used in the coating composition of the present embodiment, when it contains at least one metal (M2) selected from the group consisting of metals in Group 1 of the long periodic table, the lower limit of the total amount of the metal is preferably 0.1 ppm, more preferably 0.5 ppm, even more preferably 0.7 ppm, and particularly preferably 1 ppm, and the upper limit is preferably 12.5 ppm, more preferably 10 ppm, even more preferably 5 ppm, and particularly preferably 3 ppm. In the polycarbonate diol of the present embodiment, when at least one metal (M2) selected from the group consisting of metals in Group 1 of the long periodic table is contained, the total amount is preferably 0.1 ppm to 12.5 ppm, more preferably 0.5 ppm to 12.5 ppm, even more preferably 0.7 ppm to 12.5 ppm, particularly preferably 1 ppm to 12.5 ppm, and further preferably 0.1 ppm to 10 ppm, more preferably 0.1 ppm to 5 ppm, and particularly preferably 0.1 ppm to 3 ppm.

[0090] The (b) polycarbonate diol used in the coating composition of this embodiment has a metal (M2) content of 0.1 ppm or more in total, and when used as a coating material, the APHA value is low, and the reaction rate of curing tends to improve. In addition, the (b) polycarbonate diol used in the coating composition of this embodiment has a metal (M2) content of 12.5 ppm or less in total, and can suppress the coloring of the (b) polycarbonate diol caused by heating, and can provide a coating composition with little coloring during storage, and little discoloration when used, for example, in clear coatings for automobile exteriors, coatings for automobile interiors, coatings for home appliances, coatings for OA products, surface treatment agents for leather, surface treatment agents for synthetic leather, etc., which is more preferable.

[0091] The metal (M2) contained in the polycarbonate diol (b) used in the coating composition of this embodiment is preferably at least one metal selected from the group consisting of lithium, sodium, potassium, rubidium, cesium, and francium. Among these, at least one metal selected from the group consisting of lithium, sodium, and potassium is more preferable, and lithium is particularly preferable.

[0092] The metals contained in these polycarbonate diols may be present as residues of the polymerization catalyst, but may also be intentionally added in a predetermined amount after production.

[0093] In this embodiment, the type and amount of metal contained in the polycarbonate diol can be measured by the method described in the Examples below.

[0094] In the coating composition of the present embodiment, the mixing ratio of (a) the curing agent (organic polyisocyanate compound) and (b) the polycarbonate diol is, from the viewpoint of coating film performance, preferably such that the lower limit of the OH / NCO (equivalent ratio) is 0.2, preferably 0.3, more preferably 0.5, and even more preferably 0.7, and the upper limit is 5.0, preferably 3.0, more preferably 1.8, and even more preferably 1.3.

[0095] When the NCO is 0.2 or more equivalents relative to one OH equivalent, the curing is sufficient, so that chemical resistance, abrasion resistance, and scratch resistance are obtained, and when the NCO is 5.0 or less equivalents relative to one OH equivalent, the soft feel of the resulting coating film is improved. In this embodiment, the soft feel means that the touch is soft (flexible).

[0096] <3. Inert organic solvent> The coating composition of the present embodiment may contain an inert organic solvent as necessary to adjust the workability during coating. The amount of the inert organic solvent used is preferably 1% by mass, more preferably 10% by mass, and even more preferably 20% by mass, and preferably 90% by mass, more preferably 70% by mass, and even more preferably 50% by mass, based on the total amount of the coating composition.

[0097] When the amount of the inert organic solvent used is 1% by mass or more, the viscosity of the coating composition can be reduced, improving the workability of coating. Also, when the amount of the inert organic solvent used is 90% by mass or less, the drying time of the coating composition is shortened, and the coating thickness after coating is uniform, which is preferable.

[0098] The inert organic solvent used is not particularly limited, but is preferably an organic solvent that is substantially inert to polyisocyanate compounds and does not have active hydrogen.Examples thereof are not particularly limited, but include, for example, pentane, hexane, heptane, octane, decane, petroleum ether, petroleum benzine, ligroin, petroleum spirit, cyclohexane, methylcyclohexane, and other hydrocarbons, trichlorofluoroethane, tetrachlorodifluoroethane, perfluoroether, and other fluorinated oils, fluorine-based inert liquids, perfluorocyclohexane, perfluorobutyltetrahydrofuran, perfluorodecalin, perfluoro-n-butylamine, perfluoropolyether, dimethylpolysiloxane, and other single or mixed solvents.Furthermore, include methyl ethyl ketone, acetone, ethyl acetate, butyl acetate, toluene, xylene, and other single or mixed solvents.

[0099] <4. Additives> <4-1. Inorganic fine powder> The coating composition of the present embodiment preferably contains an inorganic fine powder in order to reduce the surface gloss and give a luxurious feel when formed into a coating film. In addition, by containing an inorganic fine powder, the tackiness of the surface of the resulting coating film can be suppressed and the soft feel is improved, which is preferable.

[0100] The inorganic fine powder is not particularly limited, but examples thereof include metal oxide fine powder, silicate compound fine powder, metal carbonate fine powder, nitride fine powder, gypsum fine powder, clay fine powder, talc fine powder, and natural mica fine powder.

[0101] Examples of metal oxide fine powders include, but are not limited to, silicon oxide fine powder, titanium oxide fine powder, aluminum oxide fine powder, zirconium oxide fine powder, etc. Examples of silicic acid compound fine powders include, but are not limited to, aluminum silicate fine powder, magnesium silicate fine powder, etc. Examples of metal carbonate fine powders include, but are not limited to, calcium carbonate fine powder, barium carbonate fine powder, etc. Examples of nitride fine powders include, but are not limited to, titanium nitride fine powder, silicon nitride fine powder, etc. These inorganic fine powders may be used alone or in combination of two or more.

[0102] The average particle size of these inorganic fine powders is preferably 4 to 15 μm, more preferably 6 to 13 μm, and even more preferably 8 to 11 μm. When the average particle size of the inorganic fine powder is equal to or greater than the lower limit, the matte effect of the resulting soft-feel paint is sufficiently exhibited, and the surface tackiness can be suppressed. When the average particle size of the inorganic fine powder is equal to or less than the upper limit, the gloss of the resulting soft-feel paint is well maintained, and the abrasion resistance and scratch resistance of the coating film are improved.

[0103] The content of these inorganic fine powders is preferably 1% by mass, more preferably 3% by mass, and even more preferably 5% by mass, and preferably 30% by mass, more preferably 20% by mass, and even more preferably 10% by mass, based on the total solid content of the coating composition. When the content of the inorganic fine powder is equal to or greater than the lower limit, the matte effect of the resulting soft-feel coating material is sufficiently exhibited, and the tackiness of the surface can be suppressed. When the content of the inorganic fine powder is equal to or less than the upper limit, the gloss of the resulting soft-feel coating material is well maintained, and the abrasion resistance and scratch resistance of the coating film are improved.

[0104] Furthermore, the content of these inorganic micropowder is preferably 1 mass% or more and 30 mass% or less, more preferably 1 mass% or more and 20 mass% or less, even more preferably 1 mass% or more and 10 mass% or less, and also preferably 3 mass% or more and 30 mass% or less, more preferably 5 mass% or more and 30 mass% or less, even more preferably 10 mass% or more and 30 mass% or less, based on the total solid content of the coating composition.

[0105] As the inorganic fine powder, silicon oxide fine powder is preferable. As the silicon oxide fine powder, hydrous or anhydrous silica fine powder is exemplified. Specific examples of such silica fine powder include, but are not limited to, "ACEMATT OK 412 (trade name)", "ACEMATT OK 607 (trade name)", "ACEMATT OK 900 (trade name)", "ACEMATT TS 100 (trade name)", "ACEMATT OK 520 (trade name)", "ACEMATT 3600 (trade name)", and "ACEMATT 3300 (trade name)" manufactured by Evonik.

[0106] <4-2. Polyurethane particles> The coating composition of this embodiment preferably contains polyurethane particles to further enhance the softness of the coating film obtained. The polyurethane particles are not particularly limited, but include spherical polyurethane particles synthesized by, for example, a method of dispersing a polyurethane prepolymer in water in the presence of a suspension stabilizer, polymerizing the polymer, washing, and drying the polyurethane (JP Patent Publication No. 1-185648), a method of emulsion-polymerizing polyurethane in a non-aqueous inert liquid in the presence of an emulsifier (JP Patent Publication No. 5-214054, JP Patent Publication No. 7-97425), etc. In the synthesis of these polyurethane particles, thermoplastic urethane particles are obtained when a bifunctional or less isocyanate urethane prepolymer is used, and three-dimensionally crosslinked urethane particles are obtained when a terminal isocyanate urethane prepolymer with more than two functionalities is used. As the polyurethane particles used in this embodiment, three-dimensionally crosslinked urethane particles are more preferably used in order to improve the acid resistance, alkali resistance, alcohol resistance, oil resistance, heat resistance, and abrasion resistance of the coating film obtained by the coating composition of this embodiment. The average particle size of the polyurethane particles used is preferably 2 to 20 μm, more preferably 4 to 15 μm, and even more preferably 5 to 10 μm. When the average particle size of the polyurethane particles is equal to or greater than the lower limit, the gloss of the resulting coating film is appropriately suppressed, and not only is a luxurious feel obtained, but the soft feel is also improved. On the other hand, when the average particle size of the polyurethane particles is equal to or less than the upper limit, the abrasion resistance and scratch resistance of the resulting coating film are improved, and the surface has a soft feel.

[0107] In the coating composition of this embodiment, the content of the polyurethane particles is preferably 1% by mass, more preferably 3% by mass, and even more preferably 5% by mass, and is preferably 30% by mass, more preferably 20% by mass, and even more preferably 10% by mass, based on the total solid content of the coating composition. When the content of the polyurethane particles is equal to or more than the lower limit, the resulting coating film has a soft feel, and when the content of the polyurethane particles is equal to or less than the upper limit, the abrasion resistance of the resulting coating film is improved.

[0108] In this embodiment, the "average particle size" refers to the volume-based average particle size (volume average particle size) measured using a laser diffraction particle size distribution analyzer (for example, SALD2100 manufactured by Shimadzu Corporation).

[0109] <4-3. Other additives> To the coating composition of the present embodiment, curing accelerators (catalysts), fillers, flame retardants, dyes, organic or inorganic pigments, release agents, flow control agents, plasticizers, antioxidants, UV absorbers, light stabilizers, defoamers, leveling agents, colorants, solvents, and the like can be added depending on various applications.

[0110] The curing accelerator is not particularly limited, but examples thereof include monoamines such as triethylamine and N,N-dimethylcyclohexylamine, diamines such as tetramethylethylenediamine, other triamines, cyclic amines, alcohol amines such as dimethylethanolamine, and ether amines. The metal catalyst is not particularly limited, but examples thereof include commonly used ones such as potassium acetate, potassium 2-ethylhexanoate, calcium acetate, lead octoate, dibutyltin dilaurate, tin octoate, bismuth neodecanoate, bismuth oxycarbonate, bismuth 2-ethylhexanoate, zinc octoate, zinc neodecanoate, phosphine, and phospholine.

[0111] The filler and pigment are not particularly limited, but for example, commonly used fillers and pigments such as woven fabric, glass fiber, carbon fiber, polyamide fiber, mica, kaolin, bentonite, metal powder, azo pigments, carbon black, clay, silica, talc, gypsum, alumina white, and barium carbonate can be used.

[0112] The release agent, flow control agent, and leveling agent are not particularly limited, but examples thereof include silicone, aerosil, wax, stearates, and polysiloxanes such as BYK-331 (manufactured by BYK Chemicals).

[0113] The additives used in this embodiment are preferably at least an antioxidant, a light stabilizer, and a heat stabilizer. These antioxidants are not particularly limited, but may be, for example, phosphoric acid, phosphorous acid, aliphatic, aromatic, or alkyl group-substituted aromatic esters, hypophosphorous acid derivatives, phosphorus compounds such as phenylphosphonic acid, phenylphosphinic acid, diphenylphosphonic acid, polyphosphonates, dialkyl pentaerythritol diphosphite, and dialkyl bisphenol A diphosphite; phenol derivatives, particularly hindered phenol compounds, sulfur-containing compounds such as thioethers, dithioacid salts, mercaptobenzimidazoles, thiocarbanilides, and thiodipropionates; and tin compounds such as tin maleates and dibutyltin monoxide. These may be used alone or in combination of two or more.

[0114] <5. Painting method> The coating method of the coating composition of this embodiment is not particularly limited, but for example, a method is used in which the components are mixed just before coating and then coated on the substrate with a spray, roll, brush, or the like. It is also possible to mix components other than the curing agent (a) in advance, add component (a) just before coating, mix uniformly, and then coat. The drying time of the coating composition of this embodiment is preferably 6 to 24 hours at room temperature, and preferably 30 minutes to 4 hours at 80°C, which is a heated atmosphere below the deformation temperature of plastics.

[0115] <6.Applications> The coating composition of the present embodiment is excellent in abrasion resistance, scratch resistance, chemical resistance, and soft feel, and is less likely to discolor, so it is suitable for use as, for example, a clear coating for automobile exteriors and a coating for automobile interiors. It can also be used preferably in the surface treatment of home appliances, office automation products, leather, and synthetic leather, etc.

[0116] <7. Paint-coated moldings> The paint-coated molding of this embodiment is a paint-coated molding obtained by applying the above-mentioned paint composition to a molding. Since the paint-coated molding of this embodiment is coated with the above-mentioned paint composition, it has the characteristics of excellent abrasion resistance, scratch resistance, chemical resistance, and soft feel, and is less likely to discolor. Because of these characteristics, the paint-coated molding of this embodiment can be suitably used as a soft-feel paint-coated molding. EXAMPLES

[0117] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. Analytical methods and evaluations of physical properties in the following examples and comparative examples were performed according to the following test methods.

[0118] <Test Method> [(b) Measurement of hydroxyl (OH) value of polycarbonate diol] Acetic anhydride (12.5 g) was diluted with pyridine (50 mL) to prepare an acetylation reagent. 2.5 to 5.0 g of sample was precisely weighed into a 100 mL eggplant flask. 5 mL of acetylation reagent and 10 mL of toluene were added to the eggplant flask using a volumetric pipette, and then a cooling tube was attached and the solution in the eggplant flask was stirred and heated at 100°C for 1 hour. 2.5 mL of distilled water was added to the eggplant flask using a volumetric pipette, and the solution in the eggplant flask was heated and stirred for an additional 10 minutes. The solution in the eggplant flask was cooled for 2 to 3 minutes, and then 12.5 mL of ethanol was added. 2 to 3 drops of phenolphthalein were added to the eggplant flask as an indicator, and then the solution in the eggplant flask was titrated with 0.5 mol / L ethanolic potassium hydroxide. As a blank test, 5 mL of acetylation reagent, 10 mL of toluene, and 2.5 mL of distilled water were placed in a 100 mL eggplant flask, heated and stirred for 10 minutes, and titrated in the same manner as above. Based on this result, the hydroxyl (OH) value of the polycarbonate diol was calculated using the following formula (IV). OH value (mg-KOH / g) = {(ba) x 28.05 x f} / e (IV) a: titer of sample (mL) b: Titration volume of blank test (mL) e: Sample mass (g) f: factor of titrant

[0119] [Number average molecular weight (Mn)] The number average molecular weight of the polycarbonate diol was calculated by the following formula (V). Number average molecular weight = 2 / (OH value × 10 -3 / 56.11) (V)

[0120] [Measurement of APHA value] According to JIS K0071-1, the Hazen color number (APHA value) was measured by comparing with a standard solution placed in a colorimetric tube. For polycarbonate diol that is solid at room temperature, it was heated to 70°C, dissolved, and the APHA value was measured. The smaller the APHA value, the less coloring is evaluated.

[0121] [Residual amount of catalyst in polycarbonate diol] Approximately 0.1 g of polycarbonate diol was weighed out and dissolved in 4 mL of acetonitrile to obtain a solution. Then, 20 mL of pure water was added to the obtained solution to precipitate polycarbonate diol, and the precipitated polycarbonate diol was removed by filtration. The filtered solution was diluted with pure water to a predetermined concentration. The metal ion concentration in the diluted solution was analyzed by ion chromatography. The metal ion concentration of acetonitrile used as a solvent was measured as a blank value, and the metal ion concentration of this solvent was subtracted from the metal ion concentration in the diluted solution to obtain the metal ion concentration of the polycarbonate diol product. The measurement conditions were as shown below. The concentrations of various metals remaining in the polycarbonate diol were determined using the calibration curves of various metals prepared in advance. High-performance liquid chromatography (HPLC) measurement conditions Equipment: Waters 2690 Column: IonPac CS12A Flow rate: 1.0ml / min Injection amount: 1.5ml Pressure: 950~980psi Column temperature: 35℃ Detector sensitivity: RANGE 200μS Suppressor: CSRS 60mA Eluent: 20mmol / l methanesulfonic acid aqueous solution

[0122] <How to evaluate coating> [Pendulum hardness] The coating solutions prepared in the examples and comparative examples were uniformly applied to a glass plate using an applicator so that the coating thickness after drying would be 40 μm. After drying at room temperature for 15 minutes, the coating film was dried in an oven at 80° C. for 2 hours, and then removed from the oven. The coating film was left in a thermostatic chamber at 23° C. for 24 hours, and then subjected to evaluation of pendulum hardness. The pendulum hardness was measured using a pendulum hardness tester (using a Konig pendulum) manufactured by BYK-Gardner. Specifically, a coating sample was placed in the device, and the time (t) from when the amplitude became 5° to when it became 2° was measured. The same measurement was performed on an uncoated glass plate, and the time (t0) from when the amplitude became 5° to when it became 2° was measured. The pendulum hardness (X) was calculated using the following formula (VI). Pendulum hardness: X=t / t0 (VI)

[0123] [Room temperature tensile test] A coating film was prepared in the same manner as in the above-mentioned <Pendulum hardness>, except that the film thickness was 0.5 mm, and a rectangular test piece having a width of 10 mm, a length of 100 mm, and a thickness of about 0.5 mm was prepared from the coating film in accordance with JIS K6301 (2010). The obtained test piece was subjected to a tensile test using a tensile tester (manufactured by Orientec Co., Ltd., product name "Tensilon, Model RTE-1210") at a chuck distance of 20 mm, a tensile speed of 100 mm / min, and a temperature of 23°C (relative humidity of 55%), and the stress (100% modulus), the strength at break, and the elongation at break were measured at the time when the test piece was elongated to 100%.

[0124] [Scratch resistance] A coating film was formed on glass using the same method as used to measure pendulum hardness. A 4-row brass brush manufactured by Industry Kowa was used to scratch the coating surface by 20 strokes parallel to the handle with a load of 100 g, a stroke speed of 30 cm / sec, and a stroke width of 5 cm. Immediately after scratching, the gloss (G1) of the scratched area was measured at an angle of 60 degrees using a variable angle glossmeter manufactured by Suga Test Instruments Co., Ltd. The initial gloss (G0) of the same area before the scratching test was used, and the scratch resistance was evaluated based on the decrease in gloss according to the following formula (VII). Gloss retention (%) = (G1 / G0) x 100 (VII) The higher the gloss retention, the more excellent the scratch resistance is evaluated to be.

[0125] [Abrasion resistance] A coating film with a thickness of 40 μm was formed on an acrylonitrile-butadiene-styrene (ABS) resin plate in the same manner as in the measurement of pendulum hardness. The abrasion resistance of the resulting coating film was measured using a Taber abrasion tester in accordance with the method of JIS K5600-5-8. The change in mass between the coated plate before the abrasion test and after the abrasion test (500 rotations) was measured and expressed.

[0126] [Evaluation of resistance to oleic acid] The coating solution prepared in the examples and comparative examples was applied onto a glass plate and heated at 80°C for 2 hours to prepare a coating film with a thickness of 0.5 mm. The coating film was peeled off from the glass plate, cut into a piece of approximately 3 cm x 3 cm, and the mass of the coating film before immersion was weighed. This coating film was placed in a 250 mL glass bottle containing 50 ml of oleic acid as a test solvent, and left to stand in a constant temperature bath under a nitrogen atmosphere at 80°C for 16 hours. After the test, the coating film was taken out and lightly wiped on both sides with a paper wiper, and then the mass was measured with a precision balance, and the mass change rate (increase rate (%)) from before the test was calculated.

[0127] [Soft feel] The coating solutions prepared in the examples and comparative examples were applied to an acrylonitrile-butadiene-styrene (ABS) resin plate to a thickness of 40 μm to obtain a coated plate. The softness of the surface of the obtained coated plate was evaluated by the feel when touched with the hand. The evaluation results were expressed as follows. ◎: Very good softness ○: Good softness △: Relatively good softness ×: Does not feel soft.

[0128] [Chemical resistance] A coating film was prepared in the same manner as in the above-mentioned <Pendulum hardness>, and a 10 mm diameter cotton ball soaked in various solvents (ethanol (EtOH), methyl ethyl ketone (MEK), xylene) was placed on the obtained coating film for 1 minute, and the condition of the coating film after removing the solvent remaining on the surface was observed. The judgment method was as follows. ○: Transparent, no dents △: Slightly cloudy or slightly dented ×: Cloudy or with dents

[0129] [Weather resistance test] To the coating solutions prepared in the Examples and Comparative Examples, 0.2% by mass of IRGANOX1076 and 0.2% by mass of TINUVIN765 were added and stirred to prepare coating solutions for weather resistance tests. These were applied to a white acrylonitrile-butadiene-styrene (ABS) resin plate using an applicator, and then heat cured at 80°C for 2 hours to obtain a coating film with a thickness of 40 μm for weather resistance tests. The obtained coating film for weather resistance test was subjected to a weather resistance test for one month using a DPWL-5R manufactured by Suga Test Instruments Co., Ltd. (black panel temperature 60°C, irradiance 30 w / m2, cycle conditions: irradiation at 60°C for 4 hours, wet at 40°C for 4 hours, ultraviolet fluorescent lamp: SUGA-FS-40). The L value, a value, and b value of the coating film were measured before and after the weather resistance test, and the color difference was calculated using the ΔE calculation method below. ΔE={(L1-L2)2+(a1-a2)2+(b1-b2)2}1 / 2 In the above formula, L1, a1, and b1 represent the L value, a value, and b value of the coating film before the weather resistance test, and L2, a2, and b2 represent the L value, a value, and b value of the coating film after the weather resistance test. The lower the ΔE value, the less coloring is evaluated.

[0130] [Compound abbreviation] The abbreviations for compounds in the following Examples and Comparative Examples are as follows. Mn(OAc)2·4H2O: Manganese(II) acetate tetrahydrate Mn(acac)2·2H2O: Manganese(II) acetylacetonate dihydrate Mn(acac)3: Manganese(III) acetylacetonate Mn(tBuCOCH2COtBu)2·2H2O: 2,2,6,6-tetramethyl-3,5-heptanedionate manganese(II) dihydrate Mn(CF3COCH2COCF3)2·2H2O: Manganese hexafluoroacetylacetonate dihydrate [Mo(acac)]2: Molybdenum(II) acetylacetonate dimer Fe(acac)3: Iron(III) acetylacetonate Co(acac)2·2H2O: Cobalt(II) acetylacetonate dihydrate Ni(acac)2·2H2O: Nickel(II) acetylacetonate dihydrate Cu(acac)2: Copper(II) acetylacetonate Ti(OBu)4: Tetra-n-butyl titanate Ti(acac)2(OiPr)2: Titanium(IV) bis(acetylacetonate) diisopropoxide Mg(acac) 2· 2H2O: Magnesium(II) acetylacetonate dihydrate Li-OMe: Lithium methoxide Na-OMe: Sodium methoxide K-OMe: Potassium methoxide Li-t-OBu: Lithium-t-butoxide EC: Ethylene carbonate DEC: Diethyl carbonate 14BDO: 1,4-butanediol 15PDO: 1,5-Pentanediol 16HDO: 1,6-Hexanediol

[0131] [Synthesis Example 1 of Polycarbonate Diol] In a 1L separable flask equipped with a stirrer, a thermometer, and a vacuum jacketed Oldershaw (15 theoretical plates) with a reflux head on top, 355g (3.00mol) of 1,6-hexanediol and 264g (3.00mol) of ethylene carbonate were charged as raw material monomers, and 13.8mg of manganese acetate (II) tetrahydrate was added as a catalyst (5ppm as metal amount relative to the total amount of all dihydroxy compounds and carbonate esters). The raw material in the flask was heated in an oil bath set at 160°C, and the raw material monomers were polycondensed by transesterification for 5 hours at an internal temperature of 140°C and a vacuum degree of 3kPa while removing a part of the distillate from the reflux head, to obtain a polycarbonate diol. Then, the distillation was switched to simple distillation, and the pressure was gradually reduced to 0.1 kPa. The temperature of the oil bath was set to 175°C, and the reaction was carried out for 3 hours at an internal temperature of 160°C in the flask, and the monomer was distilled to obtain a polycarbonate diol. After introducing nitrogen gas into the flask to normal pressure, the temperature of the oil bath was set to 125°C, and the internal temperature of the flask was set to 110 to 120°C. As a catalyst deactivator, monobutyl phosphate was added in an amount equivalent to the amount of the catalyst charged, and the mixture was stirred at a temperature of 110 to 120°C for 3 hours. The results of analyzing the obtained polycarbonate diol are shown in Table 1. The polycarbonate polyol is called PC1.

[0132] [Polycarbonate diol synthesis examples 2-10] A polycarbonate diol was obtained by polycondensing the raw material monomers through an ester exchange reaction in the same manner as in Synthesis Example 1, except that the type and amount of the catalyst added were the type and amount shown in Table 1. The analytical results are shown in Table 1. The obtained polycarbonate diols are called PC2 to PC10.

[0133] [Polycarbonate diol synthesis examples 11-13] A polycarbonate diol was obtained by polycondensing the raw material monomers by transesterification in the same manner as in Synthesis Example 1, except that the time for removing a part of the fraction from the reflux head was set to 12 hours at a vacuum degree of 3 kPa and the type and amount of the catalyst added were set to the types and amounts shown in Table 1. The analytical results are shown in Table 1. The obtained polycarbonate diols are called PC11 to PC13.

[0134] [Table 1]

[0135] [Synthesis Example 14] 355g (3.00mol) of 1,6-hexanediol and 264g (3.00mol) of ethylene carbonate were charged into a 1L separable flask equipped with a stirrer, a thermometer, and a vacuum jacketed Oldershaw type (15 theoretical plates) with a reflux head on top, and 13.8mg of manganese(II) acetate tetrahydrate and 6.7mg of lithium methoxide were added as catalysts. The raw materials in the flask were heated in an oil bath set at 170°C, and the raw material monomers were polycondensed by transesterification for 4 hours at an internal temperature of 135°C and a vacuum degree of 3kPa while removing a part of the distillate from the reflux head, to obtain a polycarbonate diol. After that, the reaction was switched to simple distillation, and the pressure was gradually reduced to 0.1 kPa. The temperature of the oil bath was set to 165°C, and the reaction was carried out for 2 hours at an internal temperature of 150°C in the flask, and the monomer was distilled to obtain a polycarbonate diol. After introducing nitrogen gas to normal pressure, the temperature of the oil bath was set to 125°C, and the internal temperature of the flask was set to 110 to 120°C. As a catalyst deactivator, monobutyl phosphate was added in an amount equivalent to the amount of the catalyst charged, and the mixture was stirred at a temperature of 110 to 120°C for 3 hours. The results of analyzing the obtained polycarbonate diol are shown in Table 2. The polycarbonate diol is called PC14.

[0136] [Polycarbonate diol synthesis examples 15-26] Polycarbonate diols were obtained by polycondensing raw material monomers through transesterification in the same manner as in Synthesis Example 14, except that the type and amount of the catalyst added were the type and amount shown in Table 2. The analytical results are shown in Table 2. The obtained polycarbonate diols are called PC15 to PC26.

[0137] [Polycarbonate diol synthesis examples 27-29] A polycarbonate diol was obtained by polycondensing the raw material monomers by transesterification in the same manner as in Synthesis Example 14, except that the time for removing a part of the fraction from the reflux head was set to 12 hours at a vacuum degree of 3 kPa and the type and amount of the catalyst added were set to the types and amounts shown in Table 2. The analytical results are shown in Table 2. The obtained polycarbonate diols are called PC27 to PC29.

[0138] [Table 2]

[0139] [Synthesis Examples 30-33] A polycarbonate diol was obtained by polycondensing the raw material monomers by transesterification in the same manner as in Synthesis Example 14, except that the dihydroxy compound and carbonate ester used were of the types and amounts shown in Table 3. The properties of the obtained polycarbonate diol are shown in Table 3. The obtained polycarbonate diols are called PC30 to PC33, respectively.

[0140] [Synthesis Example 34] A polycarbonate diol was obtained by polycondensing the raw material monomers by transesterification in the same manner as in Synthesis Example 14, except that the dihydroxy compound and carbonate ester used were of the types and amounts shown in Table 3, and the reaction time after switching to simple distillation was 0.5 hours. The properties of the obtained polycarbonate diol are shown in Table 3. The obtained polycarbonate diol is called PC34.

[0141] [Synthesis Example 35] A polycarbonate diol was obtained by polycondensing the raw material monomers by transesterification in the same manner as in Synthesis Example 14, except that the dihydroxy compound and carbonate ester used were of the types and amounts shown in Table 3, and the reaction time after switching to simple distillation was 3 hours. The properties of the obtained polycarbonate diol are shown in Table 3. The obtained polycarbonate diol is called PC35.

[0142] [Synthesis Examples 36-39] A polycarbonate diol was obtained by polycondensing the raw material monomers by transesterification in the same manner as in Synthesis Example 14, except that the dihydroxy compound and carbonate ester used were of the types and amounts shown in Table 3. The properties of the obtained polycarbonate diol are shown in Table 3. The obtained polycarbonate diols are called PC36 to PC39, respectively.

[0143] [Table 3]

[0144] [Example 1] 200g (0.1mol) of polycarbonate diol PC1, 2.06g of leveling agent BYK-331 (manufactured by BYK Chemicals), 0.8g of dibutyltin dilaurate (manufactured by Air Product), and 356g of a mixed solvent of xylene / butyl acetate (70 / 30) as a thinner were added and stirred to obtain a paint base. 38.2g of Duranate TPA-100 (manufactured by Asahi Kasei Chemicals: hexamethylene diisocyanate-based isocyanurate-type hardener, NCO content = 23.1 mass%, isocyanate group in one molecule: 3.0) was added as a hardener to this and mixed to prepare a paint solution (paint composition). This was applied to a glass plate using an applicator, and then heated and hardened at 80 ° C for 2 hours to obtain a coating film. The physical properties of the coating film and film obtained from the coating solution (coating composition) using PC1 are shown in Table 4.

[0145] [Examples 2 to 10] As shown in Table 4, except that PC2 to PC10 were used as the polycarbonate diol, coating solutions (coating compositions) were prepared in the same manner as in Example 1, and the physical properties of the coating films and films obtained from each coating solution (coating composition) were evaluated. The evaluation results are shown in Table 4.

[0146] [Comparative Examples 1 to 3] As shown in Table 4, except that PC11 to PC13 were used as the polycarbonate diol, coating solutions (coating compositions) were prepared in the same manner as in Example 1, and the physical properties of the coating films and films obtained from each coating solution (coating composition) were evaluated. The evaluation results are shown in Table 4.

[0147] [Table 4]

[0148] [Examples 11 to 23, Comparative Examples 4 to 6] As shown in Table 5, except that PC14, PC15, PC16, PC17, PC18, PC19, PC20, PC21, PC22, PC23, PC24, PC25, PC26, PC27, PC28, and PC29 were used instead of polycarbonate diol PC1, coating solutions (coating compositions) were prepared in the same manner as in Example 1, and the physical properties of the coating films and films obtained from each coating solution (coating composition) were evaluated. The evaluation results are shown in Table 5.

[0149] [Table 5]

[0150] [Examples 24 to 33] As shown in Table 6, coating solutions (coating compositions) were prepared in the same manner as in Example 1, except that PC30, PC31, PC32, PC33, PC34, PC35, PC36, PC37, PC38, and PC39 were used instead of polycarbonate diol PC1, and the physical properties of the coating film and film obtained from each coating solution (coating composition) were evaluated. The evaluation results are shown in Table 6.

[0151] [Table 6]

[0152] [Example 34] 200g of polycarbonate diol PC32, 2.06g of leveling agent BYK-331 (manufactured by BYK Chemicals), 0.8g of dibutyltin dilaurate (manufactured by Air Product), 25g of fine powder silica (ACEMATT TS 100, manufactured by EVONIK, average particle size: 9.5μm), and 356g of a mixed solvent of xylene / butyl acetate (70 / 30) as a thinner were added and stirred to obtain a paint base. 38.2g of Duranate TPA-100 (manufactured by Asahi Kasei Chemicals: hexamethylene diisocyanate-based isocyanurate-type hardener, NCO content = 23.1 mass%, isocyanate group in one molecule: 3.0) was added as a hardener and mixed to prepare a paint solution (paint composition). This was applied onto an acrylonitrile-butadiene-styrene (ABS) resin plate and then heat cured at 80°C for 2 hours to obtain a coating film with a thickness of 40 μm. The physical properties of the coating film and film obtained from the coating solution (coating composition) are shown in Table 7.

[0153] [Example 35] 200g of polycarbonate diol PC32, 2.06g of leveling agent BYK-331 (manufactured by BYK Chemicals), 0.8g of dibutyltin dilaurate (manufactured by Air Product), 25g of fine powdered silica (ACEMATT TS 100, manufactured by EVONIK, average particle size: 9.5μm), and 356g of a mixed solvent of xylene / butyl acetate (70 / 30) as a thinner were added and stirred to obtain the base paint. 37.5 g of Duranate 24A-100 (Asahi Kasei Corporation: hexamethylene diisocyanate-based biuret-type curing agent, NCO content = 23.5 mass%, isocyanate group per molecule: 3.5) was added as a curing agent and mixed to prepare a coating solution (coating composition). This was applied to an acrylonitrile-butadiene-styrene (ABS) resin plate, and then heated and cured at 80 ° C for 2 hours to obtain a coating film with a thickness of 40 μm. The physical properties of the coating film and film obtained from the coating solution (coating composition) are shown in Table 7.

[0154] [Example 36] 200g of polycarbonate diol PC32, 2.06g of leveling agent BYK-331 (manufactured by BYK Chemicals), 0.8g of dibutyltin dilaurate (manufactured by Air Product), 25g of polyurethane particles (Art Pearl, C-800, average particle size: 6μm, manufactured by Negami Chemical Industries Co., Ltd.), and 356g of a mixed solvent of xylene / butyl acetate (70 / 30) as a thinner were added and stirred to obtain a paint base. 38.2g of Duranate TPA-100 (manufactured by Asahi Kasei Chemicals: hexamethylene diisocyanate-based isocyanurate-type hardener, NCO content = 23.1 mass%, isocyanate group in one molecule: 3.0) was added as a hardener and mixed to prepare a paint solution (paint composition). This was applied onto an acrylonitrile-butadiene-styrene (ABS) resin plate and then heat cured at 80°C for 2 hours to obtain a coating film with a thickness of 40 μm. The physical properties of the coating film and film obtained from the coating solution (coating composition) are shown in Table 7.

[0155] [Table 7]

[0156] In this example, the average particle diameter of the inorganic fine powder and polyurethane particles was measured by volumetric average particle diameter measurement using a 0.25 mass% aqueous solution (aqueous dispersion) and a particle size distribution analyzer SALD-2100 manufactured by Shimadzu Corporation. [Industrial Applicability]

[0157] The coating composition of the present invention has excellent physical properties and excellent coloring stability, and therefore can provide a coating composition that shows little discoloration when used as a clear coating for automobile exteriors, a coating for automobile interiors, a coating for home appliances, a coating for office automation products, a surface treatment agent for leather, a surface treatment agent for synthetic leather, etc.

Claims

1. (a) a curing agent and (b) a polycarbonate diol, The (a) curing agent is an organic polyisocyanate compound having 2.6 or more isocyanate groups in one molecule, The (b) polycarbonate diol is a polycondensate obtained by an ester exchange reaction between a dihydroxy compound and a carbonate ester, The number average molecular weight of the (b) polycarbonate diol is 250 or more and 3000 or less, The (b) polycarbonate diol contains at least one metal (M1) selected from the group consisting of metals in Groups 6, 7, 8, 9, 10, and 11 of the long form periodic table in a total amount of 1 ppm to 25 ppm, The coating composition, wherein the polycarbonate diol (b) has a Hazen color number of 50 or less as measured in accordance with JIS-K0071-1 (1998).

2. The coating composition according to claim 1, wherein the (b) polycarbonate diol contains at least one metal (M2) selected from the group consisting of metals in Group 1 of the long periodic table in a total amount of 0.1 ppm or more and 12.5 ppm or less.

3. 2. The coating composition according to claim 1, wherein the (a) curing agent is a polyisocyanate derived from an aliphatic organic polyisocyanate compound and / or an alicyclic organic polyisocyanate compound.

4. The coating composition according to claim 1, comprising 1 to 90% by mass of an inert organic solvent.

5. 2. The coating composition according to claim 1, comprising 1 to 30 mass % of inorganic fine powder having an average particle size of 4 to 15 μm and / or polyurethane particles having an average particle size of 2 to 20 μm based on the total solid content.

6. A paint-coated molding obtained by coating a paint composition according to any one of claims 1 to 5 on a molding.

Citation Information

Patent Citations

  • Polyurethane-based resin for coating agent and coating agent composition

    JP2000095836A

  • Polyurethane coating agent

    JP2001123112A

  • Coating composition

    JP2021075632A